PENDIDIKAN PANCASILA SEBAGAI DASAR SISWA DALAM MENGAMALKAN TOLERANSI ANTAR SESAMA (STUDI KASUS: MIS HIDAYATUL MUBTADIIN MUKOMUKO) - Tri Handayani, Lilis; Maghfiroh, Annisaul (JECE (Journal of Ethics and Character Education), 2024)
Pancasila education plays a crucial role in instilling the values of tolerance among students, especially within the context of religious-based schools. The issue addressed in this study is the lack of understanding and practice of tolerance among students, which can affect their social interactions in the school environment. This research aims to analyze the implementation of Pancasila education at MIS Hidayatul Mubtadiin Mukomuko and its influence on shaping students' attitudes of tolerance. The method used in this study is a qualitative approach with a case study design, involving observation, in-depth interviews, and documentation. Data were collected from teachers, students, the school principal, and parents to explore their views on Pancasila education and its impact on tolerance. The results of the study indicate that Pancasila education at MIS Hidayatul Mubtadiin Mukomuko has been thoroughly implemented through classroom learning and daily school activities. Students demonstrated positive attitudes of tolerance, such as respecting differences and collaborating regardless of background. However, challenges remain in deeply internalizing the value of tolerance, as minor conflicts still occur among students. The novelty of this research lies in emphasizing the active role of teachers and school principals in consistently applying Pancasila values, as well as the involvement of parents and the community in supporting character education. In conclusion, Pancasila education that is based on real practices in schools can foster strong tolerance among students, although continuous reinforcement of these values is necessary.